Suboptimal entravirine activity is common during failure of nevirapine based combination antiretroviral therapy in a cohort infected with non-B subtype HIV-1 (2010)
"OBJECTIVE:The primary objective of this study was to estimate etravirine activity in a cohort of patients infected with non-B subtype HIV-1 and failing nevirapine-based therapy. MATERIALS AND METHODS:Genotypic resistance testing was performed if viral load was >OR= 1,000 copies/ml after receiving at least six months of therapy. Suboptimal response to etravirine was predicted by a score >OR= 2.5 on the Tibotec weighting schema, >OR= 4 in the Monogram schema, or classification as high to low-level resistant by a modification of the Stanford HIVdb algorithm (Version 5.1.2). Bivariate and multivariate analyses were conducted to determine the risk factors for suboptimal etravirine activity. RESULTS:The patients (n=91) were receiving nevirapine and lamivudine plus stavudine (57.1%) or zidovudine (42.9%). Median duration of nevirapine exposure was 53 weeks (IQR 46-101 weeks). The most common etravirine resistance associated mutations were Y181C (42.9%), G190A (25.3%), H221Y (19.8%), A98G (18.7%), K101E (16.5%), and V90I (12.1%). Suboptimal etravirine activity was predicted in 47.3 to 56.0%. There were disparities in mutations listed in Tibotec versus Monogram Schemas. Predicted suboptimal activity was not associated with nucleoside reverse transcriptase inhibitor (NRTI) used, gender, pretreatment or current CD4 cell count or viral load, subtype or NRTI mutations. CONCLUSION:Etravirine has compromised activity in approximately half of the patients failing nevirapine-based first-line treatment in this cohort, which supports guidelines that caution against using it with NRTIs alone in such patients. "